2017
DOI: 10.5194/acp-17-4387-2017
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the organic aerosol volatility in a boreal forest using two independent methods

Abstract: Abstract. The volatility distribution of secondary organic aerosols that formed and had undergone aging – i.e., the particle mass fractions of semi-volatile, low-volatility and extremely low volatility organic compounds in the particle phase – was characterized in a boreal forest environment of Hyytiälä, southern Finland. This was done by interpreting field measurements using a volatility tandem differential mobility analyzer (VTDMA) with a kinetic evaporation model. The field measurements were performed durin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…As a result, a OFR fate correction for S/IVOCs is not feasible. Previous field measurements and laboratory studies demonstrated that SOA from various sources were mainly ~40%-80% L/ELVOCs and ~20%-60% S/IVOCs (Hong et al, 2017;Saha et al, 2017;D'Ambro et al, 2018;Sato et al, 2018;Saha et al, 2018). In our experiments, the low-NOx yields are significantly higher than the high-NOx yields (paper in preparation), indicating a lower volatility for SOA formed under low-NOx conditions.…”
supporting
confidence: 49%
“…As a result, a OFR fate correction for S/IVOCs is not feasible. Previous field measurements and laboratory studies demonstrated that SOA from various sources were mainly ~40%-80% L/ELVOCs and ~20%-60% S/IVOCs (Hong et al, 2017;Saha et al, 2017;D'Ambro et al, 2018;Sato et al, 2018;Saha et al, 2018). In our experiments, the low-NOx yields are significantly higher than the high-NOx yields (paper in preparation), indicating a lower volatility for SOA formed under low-NOx conditions.…”
supporting
confidence: 49%
“…The chemical composition of aerosol particles at SMEAR II has been studied previously in multiple short (< 1-10 month) measurement campaigns with both offline (Saarikoski et al, 2005;Kourtchev et al, 2005;Cavalli et al, 2006;Finessi et al, 2012;Corrigan et al, 2013;Kourtchev et al, 2013;Kortelainen et al, 2017) and online methods (Allan et al, 2006;Finessi et al, 2012;Häkkinen et al, 2012;Corrigan et al, 2013;Crippa et al, 2014;Hong et al, , 2017Makkonen et al, 2014;Äijälä et al, 2017Kortelainen et al, 2017;Riva et al, 2019). The previous studies include several important discoveries regarding SMEAR II aerosol composition.…”
mentioning
confidence: 99%
“…A scanning mobility particle sizer (SMPS, TSI, Inc.) was used to measure the particle number size distribution (mobility diameter: 15-600 nm) with a time resolution of 5 min. By assuming the densities of the components obtained in the literature (Kuwata et al, 2012;Poulain et al, 2014;Hu et al, 2017), the corresponding mass concentration can be calculated from the particle number size distribution. The AE-31 and SMPS were used only for ambient sampling.…”
Section: Instruments and Methodologymentioning
confidence: 99%